Superior thermal conductivity of transparent polymer nanocomposites with a crystallized alumina membrane - Md. Poostforush; H. Azizi (eXPRESS Polymer Letters)
The properties of novel thermoconductive and optically transparent nanocomposites have been reported. The composites were prepared by the impregnation of thermoset resin into crystallized anodic aluminum oxide (AAO). Crystallized AAO synthesized by annealing amorphous AAO membrane at 1200°C. Although through-plane thermal conductivity of nanocomposites improved up to 1.13 W•m–1•K–1 (39 vol% alumina) but their transparency was preserved (Tλ550 nm ~ 72%). Integrated annealed alumina phase, low refractive index mismatch between resin and alumina and formation of nano-optical fibers through the membrane resulted in such marvel combination. This report shows a great potential of these types of nanocomposites in ‘heat management’ of lightening devices.